2022
DOI: 10.1002/apxr.202200017
|View full text |Cite
|
Sign up to set email alerts
|

Lowering of Electrostatic Actuator Driving Voltage and Increasing Generated Force Using Spontaneous Polarization of Ferroelectric Nematic Liquid Crystals

Abstract: Although electrostatic actuators have a simple structure and are lightweight, their range of application is limited because a high applied voltage of more than several kilovolts is required for practical use. Since the force acting between the electrodes of an electrostatic actuator is determined by the electric charge accumulated at the electrode/dielectric interface, the focus is on spontaneous polarization of ferroelectrics to increase the charge. As the ferroelectric material, a nematic liquid crystal mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
(81 reference statements)
1
11
0
Order By: Relevance
“…We can see that for P(VDF-TrFE-CTFE), the relationship between actuator energy density (force of the actuator) and the applied electric field is nearly linear, whereas for PVDF-HFP and BoPET, it is quadratic. This almost linear force response of PVDF terpolymers to applied voltages has been previously noted in the literature (44)(45)(46). We observed that an actuator made from PVDF-HFP achieves a higher actuator energy density above 280 V μm −1 , owing to a drop of the dielectric energy density of P(VDF-TrFE-CTFE) below the value of PVDF-HFP under high electric fields.…”
Section: Modelsupporting
confidence: 82%
“…We can see that for P(VDF-TrFE-CTFE), the relationship between actuator energy density (force of the actuator) and the applied electric field is nearly linear, whereas for PVDF-HFP and BoPET, it is quadratic. This almost linear force response of PVDF terpolymers to applied voltages has been previously noted in the literature (44)(45)(46). We observed that an actuator made from PVDF-HFP achieves a higher actuator energy density above 280 V μm −1 , owing to a drop of the dielectric energy density of P(VDF-TrFE-CTFE) below the value of PVDF-HFP under high electric fields.…”
Section: Modelsupporting
confidence: 82%
“…For instance, the metallization involving the nanocomposites is applicable in fabrication of a double-helical coil electrode toward electrostatic actuators reported in a previous study. 50 In conclusion, the Pd-decorated CNT nanocomposites are excellent catalyst and reinforcement of the mechanical strength in metallization of complexstructured 3D multifunctional materials.…”
Section: Discussionmentioning
confidence: 90%
“…Since these discoveries, research into molecular design and synthesis of N F LCs and SmA F LCs has been launched 7,[15][16][17][18][19][20][21][22] toward a clear understanding of the underlying mechanism, 23,24 and development of state-of-the-art materials based on them. 25,26 However, typical synthetic routes of LC materials are through a multistep pathway that entirely rely on the traditional solution chemical (SC) synthesis. As such, the net reaction time (NRT), excluding the purification time, takes a few, or several days to obtain target compounds.…”
Section: Introductionmentioning
confidence: 99%